PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS PENEMUAN TERBIMBING PADA MATERI SEGITIGA DAN SEGI EMPAT SISWA KELAS VII SMP NEGERI 4 MERANGIN - Ahde Fitri; Sukur (Mat-Edukasia, 2022)
Target of this research is to yield worksheets based on invention guided at items Parallelogram and is Trilateral which practical and valid. This Research type is development and research. This research use model 4-D which consist of 4 phase that is: define, design, develop, and disseminate. Worksheets based on invention guided by validity by five expert people that is mathematician, media and Indonesian language, and also learn class mathematics study. Practical seen from result of enquette sheet of practicalities and interview with student. Result of analysis at phase of validity indicate that worksheets based on invention guided which is yielded very valid. Result of enquette analysis of practicalities, and result interview with student indicate that worksheets based on invention guided which is yielded is practical. Pursuant to result of research obtained that worksheets based on invention guided by at parallelogram items and trilateral the developed have very valid and is practical.